THE YIELD OF THE CARRY TRADE STRATEGY - A. Yu. Mikhailov (Финансы: теория и практика)
The article analyzes the carry trade strategy in which, according to common definition, traders borrow a currency that has a low-interest rate and use the funds to buy a different currency that is paying a higher interest rate. The aim of this work is to form the optimal strategies and carry trade portfolio. The task of our study was to study the interdependence between the yield of the carry trade strategy and the USA stock market on the basis of a mathematical approach and offer a portfolio of currencies with the highest historical yield over the past five years. The author used the model of relative risk aversion. We analyzed data on exchange rates, forward premium and real exchange rates for the Eurozone, as well as for countries of the Organization for Economic Cooperation and Development (OECD) such as Australia, Brazil, China, Japan, New Zealand, Russia, Switzerland, the United Kingdom and the United States of America. Carry trade’s yield is not tied to standard risk factors. Popular funding currency — the yen has experienced a strong jump of volatility as a result of the 2008–2009 crisis. A possible explanation for this reversal is investors’ appetite for risk. The author concluded that the most common carry trade strategies in the period from 2009 to 2014 were formed on the basis of two financing currencies (Japanese yen and the US dollar) and three investment currencies (Australian dollar, New Zealand dollar and Chinese yuan). After 2014, the US dollar ceases to be the funding currency, giving way to the Euro. The optimal carry trade strategy is borrowing in the currencies of developed countries (EUR, JPY) and investing in the currencies of energy producing countries (RUB, BRL). There is a negative relationship between the volume of transactions based on the carry trade strategy and the yield of shares in the financing country. There is also a significant link between the yield of the carry trade strategy and the profitability of the USA stock market.